Tratamento de vinhaça utilizando coagulantes naturais - Girardi, Franciélle (2009)
The vinasse is a wastewater produced in large quantities in the processing of ethanol from sugar cane. It is produced at the ratio of 11-13 liters of vinasse for each liter of ethanol. Because to the large volume of vinasse generated by distillation of ethanol, various processes have been proposed to achieve of reduction its volume, elimination of polluting their character and their potential. These processes include the use of vinasse as fertilizer and/or to produce of biogas. The objective of the present work is to concentrate the vinasse through processes of coagulation/flocculation. This process can allow the use the thickened sludge as fertilizer or even for production of biogas and reuse the water. In this context there is an alternative process of the coagulation/flocculation which use natural coagulants: chitosan, moringa and tannin, which have the advantage of biodegradability and maintains the appropriate properties of the sludge for fertilizer and biogas production. This work reports experiments of coagulation/flocculation jar-test conducted in at temperature ~25°C, with samples of 200mL of vinasse, varying the concentration of coagulants. Jar-test experiments were carried out with an initial rapid mixing (100 rpm) followed by slowly mixing (50rpm) and then resting for sedimentation. The following parameters were measured for tested samples: color, turbidity, pH, COD, solids and some metals and macronutrient with the supernatant of the samples. The results show that natural coagulants remove about 45% of COD, 93% of color and up to 98% of the turbidity. The solids can be removed over 75%, the metals iron and copper up to 70% and removals of less than 50% were observed for calcium, magnesium, manganese and zinc. For elements related to fertilization NPK (nitrogen, phosphorus and potassium), over 50% of nitrogen and phosphorus will be incorporated into the sludge, while a lower level (30%) of potassium was present in the final sludge. These results emphasis the possible use of this technology for the production of sludge for fertilization of soil and reuse of water.